2005
DOI: 10.1038/sj.bmt.1705121
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus (CMV) infections and CMV-specific cellular immune reconstitution following reduced intensity conditioning allogeneic stem cell transplantation with Alemtuzumab

Abstract: Summary:We studied the incidence and recurrence of Cytomegalovirus (CMV) infection and reactivation in 38 recipients of Alemtuzumab reduced intensity conditioning-stem cell transplantation, and used CMV-HLA tetramer studies to discover if these events correlated with recovery of circulating CMVspecific CD8 þ T cells (cytotoxic T lymphocyte (CTLs)). The cumulative incidence of CMV infection was 60% at 1 year (95% CI, 45-78%) with a median reactivation time of 24 days (range 5-95 days). All patients with CMV rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 28 publications
5
42
0
Order By: Relevance
“…18,[39][40][41] Our findings support the previous data and expand further on the groups of pathogens to which transplant recipients are susceptible. These pathogens are often a cause of recurrent hospital admissions that affect not only the quality of life for the patient but also on health resources.…”
Section: Discussionsupporting
confidence: 81%
“…18,[39][40][41] Our findings support the previous data and expand further on the groups of pathogens to which transplant recipients are susceptible. These pathogens are often a cause of recurrent hospital admissions that affect not only the quality of life for the patient but also on health resources.…”
Section: Discussionsupporting
confidence: 81%
“…There remains debate as to the relative risk of CMV reactivation following non-myeloablative transplantations in comparison to myeloablative programmes 20 and CMV-specific T-cell immune reconstitution can occur promptly even after alemtuzumab-containing conditioning regimens. 21 In our cohort reactivation occurred only in CMV seropositive patients and confirmed similar studies showing the primacy of patient serostatus over donor graft origin in development of viraemia. 22 Relatively few studies have studied the importance of both CMV-specific CD4 þ and CD8 þ T-cell immune reconstitution in relation to reactivation risk.…”
Section: Discussionsupporting
confidence: 74%
“…[23][24][25][26][27] Though previous studies have showed similar patterns of immune reconstitution after non-myeloablative transplantation compared with myeloablative transplants, 28 the use of ATG or alemtuzumab has been shown to delay CMV-specific immune reconstitution. 8,9,10,17 In this study, the OS among patients with CMV reactivation was not significantly lower than patients without CMV reactivation. Previous published data have suggested that recipient CMV seropositivity itself was associated with higher mortality rates.…”
Section: Discussionmentioning
confidence: 73%
“…T-cell depletion of the graft and the addition of T-cell depleting agents reduce the risk of acute GVHD but also impair immune reconstitution and have been shown to be associated with a higher incidence of CMV reactivation especially among RIC transplants. [16][17][18] Although in general, the onset of CMV reactivation was not delayed among RIC transplants compared with MAC transplants, the addition of the T-cell depleting agents, alemtuzumab or ATG to the RIC protocol led to an earlier onset of CMV infection than with a standard RIC regimen. Interestingly, the use of ATG was not associated with an earlier onset of CMV reactivation in MAC transplants.…”
Section: Discussionmentioning
confidence: 99%